Falkland Islands and Dependencies Aerial Survey Expedition, 1955–57: Operations in 1956–57 (Polar Record, 1958)
During the Antarctic summer of 1956–57 the Falkland Islands and Dependencies Aerial Survey Expedition continued the work started the previous season. The Oluf Sven , carrying personnel, stores and a Bell 47-D helicopter, left Harwich on 20 October 1956 and arrived at Deception Island on 26 November. Modifications had been carried out to the ship to provide a hangar for the helicopter in one of the holds, and two hand winches had been installed to raise the machine to deck level. A sectional flight deck was carried and erected over the raked deck of the ship, but in practice it was found that the helicopter could operate with ease from the lift platform itself.